Efeito hipoalgésico de diferentes correntes elétricas em indivíduos saudáveis - Silva, Viviane Ribeiro da (Universidade Federal de São Carlos, 2021)
Transcutaneous electrical nerve stimulation (TENS), interferential current (CI) and Aussie current are different types of electrical stimulation used in the treatment of both acute and chronic pain, however it is not known if there is a difference in relation to the hypoalgesic effect and sensory comfort between them. Therefore, the aim of this study was to compare the hypoalgesic effect and sensory comfort between TENS, CI and Aussie current in healthy individuals. One hundred and twenty individuals were randomly assigned to four groups: TENS, CI, Aussie current and Placebo. The electrical stimulation was administered to the dominant forearm with a strong but comfortable intensity, for 30 minutes to the three groups of electric currents and to the Placebo group, the electrodes were positioned with the equipment turned off. The pressure pain threshold and sensory comfort were measured, respectively, with a digital algometer and visual analog scale. There was a significant segmental and extrasegmental hypoalgesic effect between the active groups compared to the Placebo group at the first 15 minutes of application. At 30 minutes, there was also a significant segmental and extrasegmental hypoalgesic effect between the active groups compared to the Placebo group. After 20 minutes of stimulation, there was no significant segmental difference between groups. And after 20 minutes of stimulation, there was a significant extrasegmental hypoalgesic effect in the active groups compared to the Placebo group. There was no significant difference in sensory comfort between the electrical currents. In conclusion, TENS, CI and Aussie current showed greater segmental and extrasegmental hypoalgesic effect during stimulation compared to Placebo and sensory comfort was similar between them.
Hypoalgesic effects of different types of electrical currents in healthy subjects
Keywords: Algometria; Limiar de dor por pressão; Dor; Estimulação elétrica nervosa transcutânea; Corrente interferencial; Corrente Aussie; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL